Factors Controlling Natural Gas Accumulation in the Southern Margin of Junggar Basin and Potential Exploration Targets - Chen, Jianping; Wang, Xulong; Sun, Yongge; Ni, Yunyan; Xiang, Baoli; Liao, Jiande (Frontiers in Earth Science, 2021)
In this paper, we discuss mainly about the accumulation conditions for natural gas in the southern margin of Junggar Basin, conduct a comparison about the accumulation conditions for natural gas between the southern margin and the Kuqa Depression of Tarim Basin, which are similar in sedimentary stratigraphy and tectonic evolution history, and located on the north and south sides of the Tianshan Mountains respectively. In recent decades, many large gas fields have been found in Kuqa Depression, but no great breakthrough has been made in the southern margin. The analytical results indicate that natural gases in the southern margin are dominated by thermogenic wet gas, and can be divided into three types, namely coal-derived gas, mixed gas and oil-associated gas, of which the former two types are dominated. The Jurassic coal measures are the main source rocks of natural gas, and the main gas generation time from this set of source rocks matched well with the formation time of the anticline structures, forming favorable conditions for accumulation of natural gas. In the western part of the southern margin, the Permian lacustrine and the Upper Triassic lacustrine-limnetic facies source rocks may also be important source rocks of natural gas, and the main gas generation time matched well with the formation time of anticline. Compared with the Kuqa Depression, the material base for hydrocarbon generation is better in the southern margin. Although the maturity of the Jurassic coal measures in the southern margin is slightly lower than that of the Kuqa Depression, the sealing capability of the cap rocks and the scale of reservoir rock are slightly inferior to those of the Kuqa Depression, the geologic conditions are still favorable for formation of large-scale oil and gas fields in the southern margin due to the deep Permian-Jurassic-Cretaceous petroleum system, which is the most favorable petroleum system for exploration of natural gas. The western part and the central part of the southern margin are favorable target areas for discovering the Jurassic coal-derived oil and gas reservoirs. The shallow Cretaceous-Neogene petroleum system is the secondary system for exploration of natural gas.